2020
DOI: 10.35885/1684-7318-2020-2-241-247
|View full text |Cite
|
Sign up to set email alerts
|

Potential Range of Bulbocodium versicolor (Ker-Gawl.) Spreng. (Colchicaceae, Liliopsida) in Russia

Abstract: The article presents a bioclimatic model of the potential range of Bulbocodium versicolor in European Russia. To build the model, we analyzed a matrix containing 166 B. versicolor localities in the studied region; the analysis was carried out in the SDMtoolbox program using the climatic paramaters from the WorldClim open database. The model demonstrates that, given the available dataset on the modern climatic conditions, B. versicolor may occur in a wider geographical range comprising, at the very leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…In contrast, the presence of frost days increased the proportion of dormancy breaking C. bulbocodium individuals. These results are in accordance with the ndings of other studies, which found that geophytes can germinate, grow, and develop better under colder conditions (Lundmark et al 2009;Khodorova et al 2010;Kashin et al 2020;Marković et al 2021). These studies agree that geophytes require a warm -cold -warm period to properly complete their life cycle.…”
Section: Weather Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, the presence of frost days increased the proportion of dormancy breaking C. bulbocodium individuals. These results are in accordance with the ndings of other studies, which found that geophytes can germinate, grow, and develop better under colder conditions (Lundmark et al 2009;Khodorova et al 2010;Kashin et al 2020;Marković et al 2021). These studies agree that geophytes require a warm -cold -warm period to properly complete their life cycle.…”
Section: Weather Parameterssupporting
confidence: 93%
“…The periods considered were: (1) early spring -peak owering period, (2) fall -owering period, (3) assimilation period of the previous year, (4) leaf growing period, (5) fall -peak assimilation period, (6) early spring -peak assimilation period, (7) period between owering and fruiting and (8) owering period. These periods were chosen as they are expected to have a main in uence on dormancy breaking (1, 2, 5), on bulb growth (3,4,6) and on reproduction (7, 8) (Nagyné 1984; Khodorova and Boitel-Conti 2013; Kashin et al 2020). Generalized linear mixed models (GLMMs) were used to test the effects of weather parameters on the dependent variables (number of owering individuals, number of detectable individuals, number of detectable individuals by leaf number category, changes between behaviour categories, the number of owering individuals compared to the total number of individuals, capsules length and production success) (Supplement Material Table 1).…”
Section: Weather Parametersmentioning
confidence: 99%